CT angiographic detection of cerebral aneurysms in patients with subarachnoid haemorrhage in a South African institution - Chisha, Mike (Division of Radiology, 2021)
Study rationale The incidence, location, morphology and size characteristics of cerebral aneurysms in patients presenting to Groote Schuur hospital with either subarachnoid haemorrhage or 3 rd nerve palsy have not been established by a formal audit. Objectives To determine the patient demographics, frequency of CT angiographic detection of cerebral aneurysms and aneurysmal characteristics in patients presenting to Groote Schuur Hospital with sub-arachnoid haemorrhage and /or 3 rd nerve palsy Materials and methods Computed tomographic angiographic reports of cerebral vessels of patients who presented either with subarachnoid haemorrhage or 3 rd nerve palsy to Groote Schuur hospital were reviewed over a 19-month period from January 2018 – July 2019. The data obtained were coded, entered and analysed using IBM SPSS version 25 software. Descriptive statistics was used to report the means, modes and frequencies. Demographic and aneurysmal data were compared with a similar period 5 years previously. Results One hundred and twenty-one aneurysms (121) were analysed in 2018 -2019 and 124 in 2013-2014. The large majority were solitary (92% in both groups), small (94% and 90%) and saccular (96% and 87%) respectively. Significantly more fusiform aneurysms (13% vs 6%) were seen in the earlier group. 8 % of patients had multiple aneurysms. Less than 1% were ‘giant' ( >20mm). The mean age of the patients was the same for both periods (47 years). The mean aneurysm body size was 5.7mm and 7.1mm and the mean body: neck ratio was 6 2.1 vs 1.8b). Themost frequent locations were the posterior communicating artery (31.4% [2018/2019], 35% [2013- 2014]), anterior communicating artery (29% [2018/2019], 18.5% [2013/2014]) and the middle Cerebral Arteries (13.2% [2018/2019], 13.7% [2013/2014]). The least common sites were the Superior Cerebellar artery (SCA) [2018/2019] and the Vertebral artery (0.8%) [2013/2014]. Conclusion This study has compared the demographics of patients presenting to Groote Schuur Hospital with CT angiographically confirmed symptomatic intracranial aneurysms over two periods (January to July) 5 years apart. Both the patient demographics and the aneurysmal architecture were consistent over these time periods. Further our findings conform to that described previously both in Southern Africa and abroad i.e aneurysms which have bled are most commonly related to the posterior communicating, anterior communicating and the middle cerebral arteries and most aneurysms are small and saccular in shape. Over the periods studied, there was no change in the number of patients presenting to Groote Schuur Hospital for CT cerebral angiography and Interventional treatment post aneurysm rupture. These data represent a baseline for future statistical comparison and the information extrapolated from this study will be useful for interventive planning and resource mobilization at our institution and within the Western Cape Department of Health.